Rethinking the Survival Stratagem of Corliss in the Search Engine by Sherman Alexie - Habib , Rumyia; Baqar, Ali; Farid , Ahmad; Mujahid , Kiran (Pakistan Journal of Humanities and Social Sciences, 2024)
The Search Engine is fundamentally a search for established individuality, a vision in the wilderness, and the meaning and definition of female protagonist Corliss. The present study explores the ways through which Native American hybridized identity survives in the white hegemonic cultural society. By using the theory of Evolution which is conceived by Charles Darwin, the research intends to highlight those characteristics of Corliss which make her a favorable species among stagnant and dormant tribal folks. Corliss’ survival strategy includes navigating and challenging the systemic oppressions faced by Indigenous communities in North America by getting rich white education. The Search Engine advocates that conflicting identity or in more apt terminology an identity that is hanging between cultures can discover harmony and be conformed through mutual respect, flexible attitude and acknowledgement at an individual level. This research reinvestigate Corliss’ journey which involves a progression from adopt to adapt to adept phase and her search for a stable identity while living in a mainstream society of Euro America. It deals with tussles and struggles of Corliss as she evolves through life in survival mode, particularly in regards to her experiences with her research of another traumatized poet Harlan Atwater. The effort to become recognized as a fully formed human being, as well as the desire to be treated with decency and equality rather than as second-class citizens is admirable. She fulfills the demands of anti-colonialist ideological identity; hence there is suppression over colonial subjects, subversion the colonialist discourse which eventually leads toward fine tuning the postcolonial identity that takes her to the desired status in the society unlike to her father and uncles.